Internal quality control in histotechnology: a daily and cross-cutting method - Lourenco, H (2019)
Internal quality control (IQC) is compulsory for laboratory certification and accreditation systems. On the subject of histotechnology, the discussion/dissemination of IQC tools would facilitate IQC implementation in routine laboratory practices, and would serve as a challenge to all professionals to develop a daily internal quality control tool in histotechnology (IQCH), cross-cutting grossing, histology, cytology, histochemistry, immunohistochemistry, and electron microscopy areas, in order to prematurely detect any deviations and, if possible, to rectify them immediately. In each laboratory area, verification steps were established (e.g. microtomy), through which deviations were identified and recorded (e.g. wrinkles/folds). In the final step, a cross-cutting classification scale is applied to samples, slides, and/or grids, according to specific area parameters and the potential interpretation impact of the recorded deviations. A qualitative/quantitative evaluation scale was obtained, which allows the classification of individual work units from Unsatisfactory/1' (presence of deviations that can influence or impede interpretation') to Very Good/5' (absence of deviations'). Any deviations observed are recorded based on a coded list. With regard to laboratory processes using samples/control tissues to validate the techniques that were conducted, an alphanumeric rating scale is applied, where the letter indicates the credibility level: from A' (max) to F' (zero).The continuous and constant use of this IQCH tool enables the identification of potential deviations and, possibly, their immediate correction. Classification of the various work units will allow the attainment of reference values that can be monitored and controlled, contributing to the improvement of individual and/or collective procedures, and promoting the involvement of every professional.